2008
DOI: 10.1111/j.1748-720x.2008.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Medical School Education in Bioethics, Health Law, and Health Economics

Abstract: Current challenges in medical practice, research, and administration demand physicians who are familiar with bioethics, health law, and health economics. Curriculum directors at American Association of Medical Colleges-affiliated medical schools were sent confidential surveys requesting the number of required hours of the above subjects and the years in which they were taught, as well as instructor names. The number of relevant publications since 1990 for each named instructor was assessed by a PubMed search. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 11 publications
0
38
0
3
Order By: Relevance
“…In a survey of AAMC medical schools in the US, hours of teaching devoted to health economics varied from nothing to over 30 hours per year (Persad et al 2008). This study also found that the majority of teachers were nonspecialists (measured by having at least one publication in the field).…”
Section: Practice Pointsmentioning
confidence: 95%
See 1 more Smart Citation
“…In a survey of AAMC medical schools in the US, hours of teaching devoted to health economics varied from nothing to over 30 hours per year (Persad et al 2008). This study also found that the majority of teachers were nonspecialists (measured by having at least one publication in the field).…”
Section: Practice Pointsmentioning
confidence: 95%
“…In response to rapidly rising health care expenditure and an increased understanding of the social and behavioural determinants of health, researchers in both the UK and US have highlighted a pressing need for health economics in medical training (Conill & Hillman 2000;MacLeod & McCullough 1994;Persad et al 2008;Russell et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of ethics education as an integral part of medical education has been acknowledged by the Liaison Committee on Medical Education (LCME), which has an accreditation standard that states, ''A medical school must teach medical ethics and human values, and require its students to exhibit scrupulous ethical principles in caring for patients, and in relating to patients' families and to others involved in patient care'' (LCME Standard ED-23) (14). These principles also apply to graduate medical education in emergency medicine.…”
Section: Accreditation Requirements In Ethics and Professionalismmentioning
confidence: 99%
“…En este estudio se analizaron las instituciones con rendimiento desde aceptable hasta excelente, en los grados tres a siete y se excluyeron las de grados uno y dos, que no se recomiendan. Los investigadores encontraron que 45% de los programas de postgrado en Odontología no ofrecían ninguna clase de enseñanza de la Bioética 36 . No encontraron diferencias entre instituciones públicas y privadas, según tuvieran o no cursos y contenidos de Bioética.…”
Section: Inserción De La Bioética En Los Planes De Estudio Como Compunclassified
“…Otros eran filósofos, eticistas, bioéticistas o formados en estudios religiosos, en leyes, psicología, antropolo- Ibídem., p. 303. 36 Ibídem., p. 287. gía cultural y literatura. Entre estos últimos, más que en los primeros, se encontró la tendencia a mantener una teoría ética específica, lo que podría responder a su formación en campos teóricos y más abstractos.…”
Section: Sobre Los Procesos De Enseñanza Aprendizajeunclassified